Beyond technology: Ethics and responsibility in the age of Artificial Intelligence - Baumgratz, Helen Cristina Minardi; Santos, Rodrigo Otávio dos (Seven Editora, 2024)
This study explores the relationship between artificial intelligence (AI) and human ethics, focusing on Ulrich Beck's "risk society" theory, highlighting the challenges and risks that AI presents in modern industrial society. The work emphasizes the need for effective governance and regulation of AI, addressing the ethical issues related to its implementation, and the importance of aligning the technology with human ethical principles. In addition, the possibility of different ideologies sharing similar core values is discussed, highlighting the integration of universal human values in the development of AI systems. The research underscores the need for accountability and transparency in automated systems decisions, and the importance of collaboration between human and artificial intelligence for safe and balanced decisions. This bibliographic and exploratory study seeks to offer new perspectives for future research at the intersection of AI and ethics. DOI:https://doi.org/10.56238/sevened2024.007-035